Does Antarctic Oscillation have links and influence precipitation over the Uruguay River Drainage Basin in Southeastern South America? - Fábio Guimarães Oliva (IWA Publishing, 2021)
This article examines the links and the influence of Antarctic Oscillation (AAO) on precipitation over the Uruguay River Drainage Basin and adjacent regions, situated in Southeastern South America. In this article, we used monthly data of AAO Index obtained from the Climate Prediction Center/National Centers for Environmental Prediction (CPC/NCEP); monthly data of 500 hPa vertical motion through omega variable (ω = Dp/Dt) and converted to vertical velocity (cm/s) from the NCEP/NCAR Reanalysis; monthly data of precipitation from the NCEP Reanalysis 2 and monthly data of precipitation rate from the CPC Merged Analysis of Precipitation (CMAP) with a latitude × longitude spatial resolution of 2.5° × 2.5°. All data are monthly means and were obtained from January 1979 to December 2008. The methodological procedures used Grid Analysis and Display System (GrADS) software to generate composites of vertical motion and precipitation rates. In the case of CMAP precipitation data, the methodology consists of applying the Aspin Welch statistical test, which verifies the statistical significance of the difference between two means using a significance level of 5%. The study region indicates a tendency to present higher (lower) mean rates of precipitation during the AAO negative (positive) phase. The vertical motion analysis results corroborate with the precipitation rates since the higher vertical motions were found during the negative phase of AAO. The statistical test showed, to some areas of Uruguay River Drainage Basin and adjacent regions, statistically significant differences between mean rates of precipitation observed in both phases of AAO. HIGHLIGHTS The study and the investigations of the Antarctic Oscillation – AAO (also called Southern Annular Mode – SAM) are relatively new in South America.; The importance of climate change and climate variability in the environmental changes, such as water supply and global and local warming.; We have few studies discussing the relations of AAO or SAM with precipitation over a drainage basin in South America.; The impacts of extreme rainfall or severe droughts in water supply and agriculture over southeastern Brazil where population increases year after year.; The importance of the study to hydroelectric power generation and to the agriculture sector, important economic activities in the study region.;